Perkecambahan Biji Dan Pertumbuhan Kecambah Varietas Sorgum (Sorghum bicolor L.) Pada Cekaman Krom Heksavalen - Kasmiyati, Sri; S, Santosa; Priyambada, Irfan Dwidja; Dewi, Kumala; Sandradewi, Rintawati (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
In contrast to other toxic trace metals, Cr has received little attention. Since valence level of chromium determines its toxicity, chromium is categorized as unique heavy metal. Chromium hexavalent (Cr6+) has the biggest toxicity among other valence levels. Seed germination and seedling growth are sensitive to heavy metal stresses. This research aimed to find out the responses of seed germination and seedling growth of 12 sorghum varieties toward Cr6+. Seed germination and seedling growth experiment was done on 12 sorghum varieties (Badik, UPCA-1, Keris, Keris M3, hegari Genjah, Gambela, Selayer, Sangkur, Mandau, Batari, Kawali, dan Numbu), planted in petridishes with Cr6+ treatment in form of chromate (K2CrO4) and dichromate (K2Cr2O7) compounds with 0, 50 and 500 mg of Cr/l concentration for a week. The parameters measured were the number of seeds germinate each day; the length of radicle and plumule, and fresh and dry weight at the end of experiment. The results showed that higher concentration of Cr6+ both in form of dichromate and chromate, significantly decreasedÂ the length of radicle and plumule, fresh and dry weight, and SVI (seedling vigor index) value. However, index germination (GI) value and percentage of germination of the 12 varieties sorgum significantly increased in the treatment of 50 mg Cr/l Cr6+ in form of dichromate and chromate. The treatment of dichromate compound showed bigger effect than chromate toward variables of seed germination and seedling growth of sorghum. It was noticed that 12 sorghum varieties possessed an integrated complex of adaptation to cope with the range of form of compound and concentration of Cr6+. Based on the responses of seed germination and seedling growth, Kawali, Hegari, Keris, Keris M3, Mandau, and Selayer varieties was more susceptible toward Cr6+ toxicity, and Sangkur, Selayer, Batari, and Numbu was more tolerant than other varieties. Keywords : chromate, dichromate, Sorghum bicolor, seedling, hexavalent chromium